Gender equality in employment in the Southern African Development Community (SADC) region - Leslie, Graham Andrew (Centre for Socio-Legal Research, 2023)
The primary objective of this dissertation is to explore the ways in which gender discrimination in employment is being combated in the Southern African ~ Development Community (SADC) · region. My original intention was to simply examine what measures were being taken in the SADC to attain gender equality at work, and analyse these in light of the various models of equality and feminist theories relevant to the labour market. However, after my initial research it became clear that this approach was unlikely to yield the expected dividends. This was so for a variety of reasons. First, the varying levels of development in the region preclude the divulgence of any hard and fast rules regarding the position of women in 'the labour market'. Second, the 'labour market' is by no means a homogenous entity in Southern Africa, making generalisations more dangerous than ever. Third, it is difficult to accurately gauge the real impact of measures being taken at the regional level on practices and policies in member states. It appears that, even where policy and legislative changes have been made, there is little or no evidence to show that the position of women in the workplace has actually improved. Most importantly, however, was the nature of equality and feminist theories themselves, which has led to the formation of the overwhelming recurring hypothesis underlying this dissertation, namely that equality is as much about the limits of the law as its potential. It was thus necessary to move away from my initial approach, which was predicated on a rather formal conception of the juridical, rights-based notion of equality, towards a much more contextual approach to the subject matter. This approach is borne of the understanding that equality for women in the Southern African labour market will not be attained in universities or parliaments alone. Rather, it is in the application of principles arising out of equality discourse to a specific context that any model purporting to attain gender equality in the workplace must ultimately stand or fall. Further, although increasing and widespread disillusionment with the 'failed notion of gender equality' has led to calls from some quarters for an end to the juridical, or rights-based, model of equality itself, I have resisted this conclusion for two reasons; namely, the lack of viable alternatives to the substantive model of equality offered by critics; and secondly, the fact that the 'hollow' nature of equality, in the sense that it has no intrinsic meaning in isolation of the context to which it is applied, renders it unsusceptible to attack. A corollary of this reasoning is, of course, that those who would hide behind the rights-based model can be properly called to account and will not be permitted to merely pay lip-service to rights-talk without supporting such propositions with meaningful evidence of clear and tangible impact in key targeted areas of intervention. Following the brief introduction in chapter one, chapter two proceeds to examine some of the relevant theoretical aspects of contemporary equality theory, including many of the issues alluded to above. Ultimately, while mindful of the various criticisms that have been levelled at the juridical notion of equality in recent years, I have argued for a substantive model of equality, insofar as it is capable of taking account of the context in which it is to be applied. It is asserted that, while criticisms have quite correctly exposed the ways in which equality discourse has actually masked entrenched patterns of gender discrimination in the labour market, none have yet successfully attacked the root of substantive equality, which calls for nothing more, or less, than the imperative to 'be equal'. Having decided to rally behind the substantive model of equality, in chapter three I set about exploring, in general terms, the environmental or contextual factors informing our modem-day understanding of gender equality in employment. In light of the conceptual findings in chapter two, this contextual enquiry is exposed as the real heart of the debate, which is dissected and examined accordingly. Starting with the universal picture as set out in the Beijing Declaration and Platform for Action 1996, chapter three looks at crucial issues informing and constituting the environment in which any conception of gender equality must take root. In particular, the impact of globalisation on women workers, the gendered aspect of statist theories and the trend towards the 'feminisation' of poverty are explored. It is here that the desirability of regional harmonisation of labour standards becomes evident, as does the need for proactive state intervention aimed at addressing persisting cycles of entrenched gender discrimination and disadvantage. Finally, the role of international institutions such as the International Labour Organisation (ILO), and the opportunities for women's empowerment in the workplace presented by collective bargaining, are highlighted. The focus then turns to the application of these contextual considerations within the SADC region itself. Chapter four explores the nature and extent of gender inequality in the labour markets of Southern Africa and looks at economic factors entrenching the feminisation of poverty throughout the region. In order to understand the range of the types of issues that are likely to be encountered in Southern Africa, country profiles are conducted on Lesotho and South Africa, which offer contrasting examples of almost polar proportions as regards economic development in the region. From the country profiles it is clear that a significant amount of intervention on the part of the state is required in order to combat the patriarchal heritage of customary and colonial law still operative throughout the region. Even where steps have been taken to ensure the eradication of sexist policies and laws, there is little evidence of direct positive impact on the lives of Southern African women. Chapter five critically examines developments underway at the regional level in the SADC, .and the SADC Employment and Labour Sector (ELS) in particular. Among other initiatives, the ELS has recently adopted a Gender Policy which sets out its plans for attaining gender equality in the workplace. Although measures such as the Gender Policy taken at the regional level are undoubtedly necessary and positive developments, much remains to be done by way of follow-up and implementation in member states. This chapter analyses these developments in light of the theoretical and contextual issues raised in foregoing chapters. In particular, from this regional perspective, the need for harmonisation of labour standards pertaining to gender equality, and a holistic approach to address the feminisation of poverty, including appropriate social protection measures, are argued for. Chapter six sets out a brief summary of the central arguments put forward in this dissertation, and provides some suggestions by way of outlook for gender equality in SADC labour markets.